Development and evaluation of poly adenosine 5′‐diphosphate‐ribose polymerase 1 immobilization‐based receptor chromatography. Issue 4 (28th December 2020) - Dou, Jianwei; Zhu, Zhongbo; Li, Yan; Yang, Shuo; Guo, Zhanzi; Li, Kangle; Ren, Cuicui; Huang, Linhong; He, Jianyu
Abstract: Yanghe decoction is a traditional Chinese medicine prescription and has been used for breast cancer treatment for many years. However, the effective ingredients in the decoction have not been identified. The expression of poly(ADP‐ribose) polymerase‐1 is highly related to breast cancer. Using poly(ADP‐ribose) polymerase‐1 as a probe, we expressed the haloalkane dehalogenase‐tagged protein in BL21(DE3) E. coli, immobilized it on hexachlorocaproic acid‐modified macroporous silica gel, and established a poly(ADP‐ribose) polymerase‐1 chromatographic model. The feasibility of the model was verified by testing the retention behaviors of five drugs on the protein column. We applied the model in screening the bioactive components in yanghe decoction. Rutin, liquiritin, and a compound ([M‐H] – 681.7) were identified to be the potential bioactive ingredients. We studied the binding property between rutin and poly(ADP‐ribose) polymerase‐1 by injection amount dependent method, competitive studies, and molecular docking. We found that rutin can bind to the protein through the typical inhibitor binding site of the protein. Therefore, the chromatographic model is a useful tool to screen bioactive compounds from traditional Chinese medicine. The method is fast, reliable, and applicable to other functional proteins that can screen the potential lead compounds for the treatment of the related diseases.